Attitudes toward and beliefs about prenatal HIV testing policies and mandatory HIV testing of newborns among drug users. - Fielder, Odicie; Altice, Frederick L (AIDS & public policy journal, 2005)
Controversy remains about perinatal HIV testing in many clinical settings. We sought to examine the attitudes and health beliefs among drug users about mandatory HIV testing of newborns and about voluntary versus mandatory testing of pregnant women. We also examined to what extent negative experiences and stigmatization affected attitudes toward HIV testing.
Keywords: Adolescent; Adult; AIDS Serodiagnosis; Attitude to Health; Connecticut; Female; Focus Groups; Humans; Infant, Newborn; Longitudinal Studies; Male; Mandatory Testing; Middle Aged; Neonatal Screening; Prenatal Diagnosis; Public Opinion; Substance Abuse, Intravenous